2022
DOI: 10.1101/2022.08.18.504385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational optimization of a transcription factor activation domain inhibitor

Abstract: Transcription factors are among the most attractive therapeutic targets, but are considered largely undruggable. Here we provide evidence that small molecule-mediated partitioning of the androgen receptor, an oncogenic transcription factor, into phase-separated condensates has therapeutic effect in prostate cancer models. We show that the phase separation capacity of the androgen receptor is driven by aromatic residues and short unstable helices in its intrinsically disordered activation domain. Based on this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 112 publications
3
10
0
Order By: Relevance
“…While our analysis is necessarily retrospective and correlative, it is in line with prior experimental work. , To explore this observation further, we performed all-atom simulations using the ABSINTH implicit solvent model of the p53 with three phosphomimetic mutations (S15E, T18E, and S20E) and compared the result to previous simulations of the wildtype sequence (Figure A) . While glutamic acid is an imperfect analogue for the phosphate group, the results revealed that relatively modest changes in linear charge density can cause local and long-range changes in the...…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…While our analysis is necessarily retrospective and correlative, it is in line with prior experimental work. , To explore this observation further, we performed all-atom simulations using the ABSINTH implicit solvent model of the p53 with three phosphomimetic mutations (S15E, T18E, and S20E) and compared the result to previous simulations of the wildtype sequence (Figure A) . While glutamic acid is an imperfect analogue for the phosphate group, the results revealed that relatively modest changes in linear charge density can cause local and long-range changes in the...…”
Section: Resultssupporting
confidence: 74%
“…Comparison of changes in local and global dimensions for wildtype vs phosphomimetic versions of p53. (A) Scaling maps where inter-residue distances for the phosphomimetic version of the p53 N-terminal domain (p53 ) are normalized by distances for the wildtype protein. Despite differing by only three residues in the N-terminal quarter of the protein, the phosphomimetic version of p53 shows substantial differences in long-range and local dimensions, as shown by the emergence of both attractive (blue) and repulsive (red) interactions.…”
Section: Resultsmentioning
confidence: 99%
“…2f). These results indicate that, as observed for other intrinsically disordered proteins rich in aromatic residues [21][22][23] , the number and patterning of His residues determine the phase separation propensity of nCPEB4-NTD. In addition, they suggest that a decrease in pH leads to an increase in phase separation propensity by allowing protonated His side chains to engage in cation-π or electrostatic interactions as the cationic moiety.…”
Section: Ph Fluctuations Upon Neuron Depolarization Regulate Ncpeb4 C...supporting
confidence: 65%
“…While our analysis is necessarily retrospective and correlative, it is in line with prior experimental work 57,7275 . To explore this observation further, we performed all-atom simulations using the ABSINTH implicit solvent model of the p53 1-91 with three phosphomimetic mutations (S15E, T18E, S20E) and compared the result to previous simulations of the wildtype sequence ( Fig.…”
Section: Resultsmentioning
confidence: 57%